Effect of antihypertensive treatment with lercanidipine on endothelial progenitor cells and inflammation in patients with mild to moderate essential hypertension. (1st November 2016) - De Ciuceis, Carolina; Rossini, Claudia; Tincani, Angela; Airò, Paolo; Scarsi, Mirco; Agabiti-Rosei, Claudia; Ruggeri, Giuseppina; Caimi, Luigi; Ricotta, Doris; Agabiti-Rosei, Enrico; Rizzoni, Damiano
Abstract: Background: It has been demonstrated that circulating endothelial progenitor cells (EPCs) number reflects the endogenous vascular repair ability, with the EPCs pool declining in presence of cardiovascular risk factors. Several drugs, including dihydropyridine calcium channel blockers, have been reported to elicit antioxidant and anti-inflammatory properties, as well as to improve vascular remodeling and dysfunction. However, no data are available about the effects of lercanidipine on EPCs. The aim of the present study was therefore to investigate the effects of short-term treatment with lercanidipine on circulating EPCs, as well as on indices of inflammation and oxidative stress. Patients and methods: Twenty essential hypertensive patients were included in the study and treated for 4 weeks with lercanidipine 20 mg per day orally. Investigations were performed in basal condition, after appropriate wash out of previous treatments, and after 4 weeks of lercanidipine treatment. Inflammatory and oxidative stress markers were assessed by ELISA technique. Lin-/7AAD-/CD34+/CD133+/VEGFR-2 + and Lin-/7AAD-/CD34+/VEGFR-2 + cells were identified by flow cytometry and considered as EPCs. EPCs cells were expressed as number of cells per million Lin-mononuclear cells. Results: Circulating EPCs were significantly increased after lercanidipine treatment (CD34+/CD133+/VEGFR-2 + cells: 78.3 ± 64.5 vs 46.6 ± 32.8; CD34+/VEGFR-2+: 87996 ± 165116 vs 1026 ± 1559, respectively, p < 0.05). A modest reduction in circulating indices of inflammation was also observed. Conclusions: In conclusion, lercanidipine is able to increase the number of circulating EPCs, possibly through a reduction of low-grade inflammation.